Kolaborasi Pemerintah Desa dan Komunitas dalam Pengembangan Kampung Nusantara di Desa Cintakarya Kecamatan Parigi Kabupaten Pangandaran - Hilya Auliya; Dini Yuliani; Regi Refian Garis (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This research is motivated by the importance of synergy between the village government and the community in supporting local potential-based development. Kampung Nusantara, as one of the innovative programs in Cintakarya Village, Parigi District, Pangandaran Regency, requires solid cooperation between both parties for effective and sustainable village development. However, in its implementation, collaboration between the village government and the community still faces various challenges that hinder the optimization of Kampung Nusantara development. The problem raised in this research is the suboptimal collaboration between the village government and the community in Kampung Nusantara development. This study aims to explore and analyze the factors that influence this collaboration, as well as to provide recommendations for improving the effectiveness of this collaboration. The research method used is a descriptive qualitative approach with a case study approach. Data collection was conducted through in-depth interviews, direct observation, and analysis of related documents. The findings of this study reveal that collaboration between the village government and the community in Cintakarya Village is still not running systematically and structured. Obstacles faced include a lack of coordination between the government and the community, the absence of regulations that clearly regulate the roles of each party, and limited human resource capacity in implementing the program. Nevertheless, there have been positive efforts, including the establishment of joint communication forums, capacity-building training, and support from external programs implemented by supporting institutions. This study recommends increasing the intensity of communication between village governments and communities, clarifying the roles and responsibilities of each party, and strengthening village institutions to achieve more effective collaboration. Furthermore, improving human resource capacity and establishing clear regulations are crucial to supporting the sustainability of the Kampung Nusantara program in the future.